DEVELOPING ENGLISH READING MATERIAL OF DESCRIPTIVE TEXT FOR GRADE X STUDENTS OF FASHION DESIGN STUDY PROGRAM AT SMKN 1 STABAT - Anggraini Anggraini; Masitowarni Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This research focuses on how reading text materials for the fashion design study program at SMKN 1 Stabat are created. The goal of this project was to provide English reading materials with descriptive language that were appropriate for students in the fashion design program's grade X. The study focused on grade X students at SMK N 1 Stabat, which had a total of 33 students. Questionnaires and interviews were used to gather information. The writer deduced the students' need to study English based on their school program after examining the data. Based on the needs analysis of the students, it was discovered that several reading elements from the students' book are incompatible with the syllabus. Then there's the reading material, which should be tailored to their syllabus and needs. The reading materials were completed after the materials had been designed. The total findings reveal that the new reading material received 95.8% from the Expert– lecturer and the Expert–English instructor, and that the categorization is "relevant" as the reading material criteria. The instructional materials generated were connected to the students' major, which was a fashion design degree. Gathering information and data, analyzing data, designing new reading material, validating expert, refining new reading material based on expert suggestions, and developing reading material were the six stages of material development (final product).Keywords: Reading Text Materials, Fashion Design, Descriptive Text, Research and Development (R&D)